The biofilm-positive Staphylococcus epidermidis isolates in raw materials, foodstuffs and on contact surfaces in processing plants - Schlegelová, J; Babák, V; Holasová, M; Dendis, M (Folia microbiologica, 2008)
Isolates from the "farm to fork" samples (182 isolates from 2779 samples) were examined genotypically (icaAB genes) and phenotypically (in vitro biofilm formation, typical growth on Congo red agar; CRA) with the aim to assess the risk of penetration of virulent strains of Staphylococcus epidermidis into the food chain. The contamination of meat and milk products was significantly higher in comparison with raw materials. Contamination of contact surfaces in the meat-processing plants was significantly lower than that of contact surfaces in the dairy plants. The ica genes (which precondition the biofilm formation) were concurrently detected in 20 isolates that also showed a typical growth on CRA. Two ica operon-negative isolates produced biofilm in vitro but perhaps by an ica-independent mechanism. The surfaces in the dairy plants and the milk products were more frequently contaminated with ica operon-positive strains (2.3 and 1.2 % samples) than the other sample types (0-0.6 % samples).
Keywords: potravinářská mikrobiologie; pulzní gelová elektroforéza; masné výrobky; mléčné výrobky; Virulence; Food Handling; Electrophoresis, Gel, Pulsed-Field; zvířata; virulence; Meat; Operon; Food Microbiology; kontaminace zdravotnického vybavení; Cattle; biofilmy; Milk; kontaminace potravin; manipulace s potravinami; Food Contamination; maso; skot; Dairy Products; Animals; Meat Products; operon; mléko; Equipment Contamination; Staphylococcus epidermidis; Biofilms